Flash Interactive Media to Improve the Mastery of Light Properties Concept - Widyaningsih, Mitasari; Samsudi, Samsudi; Ellianawati, Ellianawati (Universitas Negeri Semarang, 2020)
The purpose of this study is to analyze the effect of flash interactive media in improving students' understanding of concepts in elementary schools. This type of research was mixed methods with an embedded experimental model design. Quantitative data analysis techniques on the variable understanding of the concept, namely the results of the analysis of the students' pretest and posttest questions by using paired sample t-test. The results of the analysis are then triangulated with the qualitative Focus Group Discussion (FGD) data and the results of the interviews. This study involved 54 students who were selected by using the nonprobability sampling technique: purposive sampling. The population consists of 31 public schools and 13 private schools. The results of this study show a significant increase in the concept of understanding in the form of an increase in the average score understanding of concepts by 17.82%. According to questionnaire data that has been distributed, teachers and students respond very well to learning using the flash interactive media. Students' motivation to learn accompanies an increase in their understanding of concepts. It appears that the application of flash interactive media in science learning has a positive impact on increasing motivation that has an impact on increasing students' conceptual understanding.